The impact of alcohol on HIV prevention and treatment for South Africans in primary healthcare - Michelle Schneider; Matthew Chersich; Marleen Temmerman; Olivier Degomme; Charles D. Parry (AOSIS, 2014)
Background: Antiretroviral treatment (ART) has substantially reduced morbidity and mortality for HIV patients. In South Africa, with the largest ART programme globally, attention is needed not only on the further expansion of ART coverage, but also on factors which undermine its effectiveness, such as alcohol use. Objective: Given the decentralised approach of nurse-initiated and -sustained ART in the South African primary health sector, it is important to document key aspects of alcohol use to be conveyed to HIV-positive individuals and those at risk for HIV. Method: This study comprised a narrative review of relevant literature. Results: Alcohol acts through both behavioural and physiological pathways to impact on the acquisition, further transmission and then progression of HIV disease. Besides links to risky sex, alcohol undermines the immune system, raising susceptibility to contracting and then countering HIV and other infections. There are important drug interactions between alcohol and ART, or therapies for opportunistic infections and other co-morbidities. Moreover, alcohol undermines adherence to the medication which is essential for effective ART. Conclusion: Primary healthcare clinic attendees need evidence-based information on the detrimental effects of alcohol consumption on HIV infection, which ensue throughout the clinical course of HIV. This spans the role of alcohol consumption as a risk factor for HIV infection, HIV replication in infected individuals, a person's response to HIV infection and HIV treatment. Primary healthcare workers, especially nurses and HIV counsellors, require training in order to screen for and provide appropriate interventions for HIV-positive patients, those on treatment and treatment-naïve patients, who will benefit from reduced alcohol consumption or the cessation thereof.